The Effect of STEM (Science, Technology, Engineering, and Mathematics) Learning Model on Critical Thinking Ability of Students on Colloid Material - Lasim, Windi Sulistiyani; Musa, Weny J.A; Mohamad, Erni; Laliyo, Lukman Abdul Rauf; Iyabu, Hendri; Sihaloho, Mangara (Universitas Negeri Gorontalo, 2025)
This research focuses on Natural Science learning, especially colloid material, where teaching is still dominated by the lecture method. Learning models that encourage students to make direct observations through experiments are rarely applied. This causes students to be less trained in solving problems, so their critical thinking skills are not optimally developed. This study aims to determine the effect of STEM (Science, Technology, Engineering, and Mathematics) learning model on students' critical thinking skills on colloid material at SMA Negeri 1 Telaga. The research design used was pre-experiment with one group pre-test post-test design. The research sample consisted of 29 students selected by census/total sampling. Data collection was done through critical thinking skills test. The results showed that the average percentage of students' critical thinking skills in the pre-test was 46.11%, which was in the medium category, and in the post-test it increased to 83%, which was in the very high category. This shows that the STEM learning model can improve students' understanding and critical thinking skills. The statistical test shows a significance value of 0.000 < 0.05, which means H1 is accepted and H0 is rejected. Thus, it can be concluded that the STEM learning model has a positive influence on students' critical thinking skills.